VD_FINDINFO HC / 2015 / 285 vom 17. März 2015 - VD Tribunal cantonal (2015)
AVANCE DE FRAIS, DEMANDE RECONVENTIONNELLE | 224 al. 1 CPC (CH), 96 CPC (CH), 98 CPC (CH), 23 al. 1 TFJC (2010), 9 al. 1 TFJC (2010)